Analisis Perlindungan Hukum Kontrak Waralaba di Indonesia: Studi Kasus Kemitraan Franchise Indomaret - Angga Prabowo (Lembaga Pengembangan Kinerja Dosen, 2025)
The franchise business model has experienced rapid growth in Indonesia, particularly in the food, beverage, and modern retail sectors, such as Indomaret. The franchise system provides efficient business expansion opportunities for franchisors and franchisees to participate in businesses that already have established operational standards and market reputations. However, behind this development, significant legal challenges have emerged, particularly related to the unequal position between franchisors and franchisees in franchise agreements. This study aims to analyze the forms of legal protection for franchisees by reviewing the principles of fairness, balance, and legal certainty in the implementation of franchise contracts. The approach used is a normative juridical method with a case study of the Indomaret franchise partnership, which is examined through an analysis of related laws and regulations, such as Government Regulation Number 42 of 2007 concerning Franchising and Regulation of the Minister of Trade Number 71 of 2019. The results of the study indicate that there is still asymmetry of power in contract drafting, weak legal literacy of franchisees, and a lack of government oversight of agreement implementation. Therefore, regulatory reform and strengthening of oversight mechanisms are needed to ensure that franchise relationships operate fairly, transparently, and sustainably